Labor unionization structure, innovation and welfare - Tien-Der, Han; Mukherjee, Arijit (Mohr Siebeck, 2017)
We show the effects of cooperation among the labour unions with complementary workers on innovation, consumer surplus and welfare. Although cooperation among the unions reduces wage, it may either increase or decrease the firm’s incentive for innovation, and may also make the consumers and the society worse off by reducing innovation. While cooperation (compared to non-cooperation) among the unions makes the workers better off, it may not make all final goods producers better off.